Bacaan-Bacaan dalam Shalat: (Kajian Bahasa dan Nilai-Nilai Pendidikan) - Abdul Kosim (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This research is about: "Readings in Prayer" is motivated by the main paradigm that prayer is the most important worship in Islam. Every Muslim must always improve the quality of his prayer, one of which is by understanding and exploring the readings in prayer in terms of language and depth of meaning. This study aims to determine the meanings contained in the prayer readings and the educational values ​​in the form of moral messages contained therein. The results of this study are expected to provide benefits to the community, especially Muslims to make prayer the main worship that is able to give birth to significant changes in the spiritual, moral, and social domains. This research was conducted with a descriptive-qualitative method by explaining the readings in prayer scientifically and in depth. This research was systematically carried out by collecting data, analyzing data, and presenting the results of the analysis. Readings in prayer contain very interesting linguistic values, from aspects of phonology, morphology, syntax, and semantics. Educational values ​​in prayer readings contain takbir, tahmid, tasbih, istigfar, taslim, and prayer.